Ginette Reno - Chanonat, Michelle (Éditions des Intouchables, 2013)
Ginette Reno est l'une des plus grandes chanteuses de toute l'histoire du Québec. C'est aussi la personnalité dont on a le plus parlé au cours des cinquante dernières années. Ses deux mille chansons, ses trente-huit albums et ses rôles au cinéma et à la télévision ont fait d'elle une véritable icône.

"The Cult of the Diva" – Rufus Wainwright as Opera Queen - Smith, Oliver C. E. (Transposition. Musique et Sciences Sociales, 2013)
The music of Rufus Wainwright has been afforded much critical acclaim thanks to the singer-songwriter’s understanding of Queer cultural history, and the candor with which he explores (homo)sexuality in his music. This case study seeks to examine his use of opera in particular, and how Wainwright uses the historical trope of the opera queen to incorporate his own queerness into music, thus asserting an authority of difference and challenging the dominant (hetero)norm constructions of masculinity in popular music. Wainwright disregards any cultural framework imposed by heternormativism, and reclaims the Orphic figure of operatic authority as one of queer power through this absence. By drawing on his own relationship with opera, Wainwright exploits the right this gives him by reinterpreting cultural history, and revising the pejorative stereotype that is an opera queen.
Keywords: Eurydice; Hallelujah; Jeff Buckley; Memphis Skyline; Rufus Wainwright; Waiting For A Dream; Want Two; diva; gay; heteronormativism; identity; masculinity; opera; queer; stereotype

Diane Dufresne - Villeneuve, Anne-Marie (Paroles de femmes, 2013)
Croyez-vous que chaque individu a le devoir de trouver sa vocation ? Vous trouvez-vous douée pour le bonheur ? Peut-on se préparer à la souffrance ? Avez-vous déjà regretté d'être née femme ? Y a-t-il des choses qui vous révoltent actuellement dans notre société ? Voilà un aperçu du type de questions qui ont été posées à nos cinq personnalités publiques. Des questions qui demandent temps et réflexion, mais ô combien nécessaires pour faire le point sur le chemin parcouru et pour porter un regard philosophique sur l'avenir.